Safety evaluation of the food enzyme triacylglycerol lipase from the genetically modified Aspergillus luchuensis strain FL108SC - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal, 2023)
Abstract The food enzyme triacylglycerol lipase (triacylglycerol acylhydrolase; EC 3.1.1.3) is produced with the genetically modified Aspergillus luchuensis strain FL108SC by Advanced Enzyme Technologies Ltd. The genetic modifications do not give rise to safety concerns. The food enzyme is free from viable cells of the production organism and its DNA. It is intended to be used in an immobilised form for the production of modified fats and oils by interesterification. Genotoxicity tests did not raise safety concerns. The systemic toxicity was assessed by means of a repeated dose 90‐day oral toxicity study in rodents. The Panel identified a no observed adverse effect level (NOAEL) at the highest dose of 774 mg TOS/kg body weight per day. As the food enzyme is used in an immobilised form and as any residual amounts of the food enzyme‐total organic solids (TOS) are removed during the food manufacturing process, dietary exposure was not calculated. A search for the similarity of the amino acid sequence of the food enzyme to known allergens was made and no match was found. The Panel considered that a risk of allergic reactions upon dietary exposure cannot be excluded, but the likelihood is low. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns under the intended conditions of use.